Architectural hallmarks of the pluripotent genome. Issue 20 (6th May 2015) - Bouwman, Britta A.M.; de Laat, Wouter
Abstract : Pluripotent stem cells (PSCs) have the ability to self‐renew and are capable of generating all embryonic germ layers (Evans and Kaufman, 1981; Thomson et al., 1998). PSCs can be isolated from early embryos or may be induced via overexpression of pluripotency transcription factors in differentiated cells (Takahashi and Yamanaka, 2006). As PSCs hold great promise for regenerative medicine, the mechanisms underlying pluripotency and induction thereof are studied intensively. Pluripotency is characterized by a unique transcriptional program that is in part controlled by an exceptionally plastic regulatory chromatin landscape. In recent years, 3D genome configuration has emerged as an important regulator of transcriptional control and cellular identity (Taddei et al., 2004 [4]; Lanctot et al., 2007 [5]; Gibcus and Dekker, 2013; Misteli, 2009 [7]). Here we provide an overview of recent findings on the 3D genome organization in PSCs and discuss its putative functional role in regulation of the pluripotent state.